The "velocity barrier" in giant slalom skiing: implication of force production/application capacities - Chollet, M.; Delhaye, C.; Samozino, P.; Bowen, M.; Morel-Prieur, B.; Hintzy; F. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The alpine skier`s main "motor" is the potential energy, skiing velocities may require muscle forces exceeding the skier`s physical capacities. Some authors suggest that skiers have a "velocity barrier" (VB) above which performance worsens. Nevertheless, this concept has never been experimentally tested. The aim of this study was to experimentally test the existence of the VB and clarify its relationship with force production/applications capacities.